Frequency and prognostic impact of right ventricular involvement in acute myocardial infarction. (25th November 2020) - Stiermaier, T; Backhaus, S.J; Matz, J; Koschalka, A; Kowallick, J.T; De Waha-Thiele, S; Desch, S; Hasenfuss, G; Thiele, H; Eitel, I; Schuster, A
Abstract: Background: Right ventricular (RV) involvement complicating myocardial infarction (MI) is thought to impact prognosis, but potent RV markers for risk stratification are lacking. Purpose: To assess the frequency and prognostic implications of concomitant structural and functional RV injury in MI. Methods: Cardiac magnetic resonance (CMR) was performed in 1235 patients with MI (STEMI: n=795; NSTEMI: n=440) 3 days after reperfusion by primary percutaneous coronary intervention. Central core laboratory-masked analyses included structural (edema representing reversible ischemia, irreversible infarction, microvascular obstruction [MVO]) and functional (ejection fraction, global longitudinal strain [GLS]) RV alterations. The clinical endpoint was the 12-month rate of major adverse cardiac events (MACE). Results: RV ischemia and infarction were observed in 19.6% and 12.1% of patients, respectively, suggesting complete myocardial salvage in one-third of patients. RV ischemia was associated with a significantly increased risk of MACE (10.1% versus 6.2%; p=0.035), while patients with RV infarction showed only numerically increased event rates (p=0.075). RV MVO was observed in 2.4% and not linked to outcome (p=0.894). Stratification according to median RV GLS (10.2% versus 3.8%; p<0.001) but not RV ejection fraction (p=0.175) resulted in elevated MACE rates. Multivariable analysis including clinical and left ventricular MI characteristics identified RV GLS as an independent predictor of outcome (hazard ratio 1.05, 95% confidence interval 1.00–1.09; p=0.034) in addition to age (p=0.001), Killip class (p=0.020), and left ventricular GLS (p=0.001), while RV ischemia was not independently associated with outcome. Conclusions: RV GLS is a predictor of post-infarction adverse events over and above established risk factors, while structural RV involvement was not independently associated with outcome. Funding Acknowledgement: Type of funding source: None